The Informed Consent in developing countries is truly autonomous? A descriptive study of participants in a helmintiasis clinical trial - Lobato, Lucas; Gazzinelli, Maria Flávia (Acta Bioethica, 2015)
This study demonstrates that the signing of the consent form is not an autonomous decision to all participants in a clinical trial of helminths. The results of this study show that the majority of participants in a clinical trial unaware various information about the research and their rights. The lack of such information is influenced by the individual characteristics of these participants, being negatively associated with age of the research participants and positively by monthly income, access to electronic media and formal education. We conducted a descriptive study, with 70 participants in a clinical trial conducted on helminths in the Northeast of Minas Gerais. We used multiple linear regression analysis of the association. The results of this study point to the need to create strategies to improve knowledge of clinical trial participants, particularly those with individual characteristics that act as barriers to this knowledge.